Impact of the COVID-19 Pandemic on Health-Related Quality of Life, Anxiety, and Training Among Young Gastroenterologists in Romania - Ungureanu, Bogdan Silviu; Vladut, Catalina; Bende, Felix; Sandru, Vasile; Tocia, Cristina; Turcu-Stiolica, Razvan-Aurelian; Groza, Andrei; Balan, Gheorghe G.; Turcu-Stiolica, Adina (Frontiers in Psychology, 2020)
The novel COVID-19 infection has spread all over the world and is still generating a lot of issues at different levels. There is a lack of control in disease early diagnosis and rapid evolution, which impacts both the medical and the economic system. Young gastroenterologists should adapt to overcome current difficulties and continue their life and general training. This is a multi-center national study, which aims to assess the general perspective of young gastroenterologists (residents and young specialists) from six university centers in Romania regarding their current training and the psychological effect the pandemic has on their life and job. An online survey with 58 items was distributed using Google Forms, and quality of life and anxiety were assessed. The validated instruments 15D (for assessing the health-related quality of life) and endler multidimensional anxiety scales (EMAS—for assessing anxiety) were used. All analyses were performed using SPSS 25. Of the 174 gastroenterologists approached, 96 (response rate of 55%) responded. A majority of the respondents were residents in gastroenterology (64%), and 40.6% were male. The pandemic influenced the number of examined patients as well as young gastroenterologists’ endoscopy training. Health-related quality of life was negatively associated with the level of anxiety generated by the cognitive component of anxiety as a state, the new and ambiguity of the state, and how threatened the respondent felt. The level of anxiety was moderate (median = 51), and no difference was found between the physicians working in a designated hospital or not. General caution should be considered for young gastroenterologists’ training, and continuous observation should be done to ensure better mental health on the current evolution. These findings would need to be verified in larger-sample studies and in different types of specialties.